DEVELOPMENT OF BIOTECHNOLOGY TEACHING MATERIALS BASED ON HYDROPONICS RESEARCH SYSTEM WICK TO INCREASE CREATIVITY AND TECHNOLOGICAL LITERACY IN CLASS IX LEARNERS AT SMP NEGERI 2 MAJALENGKA - Oneng Kadarsih; Asep Ginanjar Arif; Sulistyono Sulistyono (Indonesian Journal of Learning and Instruction, 2022)
The purpose of this research is to develop teaching materials so that they can be utilized and implemented to students to increase creativity and technological literacy. The method used in development is Research and Development (R & D) with stages of conducting analysis, design (design), development (development), revision, implementation. The sample in this study was class IX G learners as many as 10 people and class IX J consisting of 30 people. The results of validation of LKPD Biotechnology based on Hydroponics Research System Wick is very good and very feasible to use. The student's response to LKPD Biotechnology based on Hydroponics Research System Wick obtained an excellent category. The results of student creativity obtained a very high category, with a significant increase. Meanwhile, the results and analysis of Technological Literacy with IBM SPSS 25 showed significant results between the average pretest and posttest values of the experimental group and the control group through the independent t sample test. The test result of the experimental class's N-Gain score resulted in the high category, meanwhile N-Gain score in the control class gained medium category. Thus, it can be concluded that the use of teaching materials in the form of LKPD based on hydroponics research system wick is very effective to improve technological literacy in conventional biotechnology materials utilizing modern agricultural fields in class IX students of State Junior High School 2 Majalengka for the 2021/2022 semester 2.Keywords: teaching materials; Biotechnology; Hydroponics System Wick; creativity; technological literacy.